2015
DOI: 10.1111/ssqu.12169
|View full text |Cite
|
Sign up to set email alerts
|

God and Marriage: The Impact of Religious Identity Priming on Attitudes Toward Same‐Sex Marriage*

Abstract: Objective. We hypothesize that priming a shared in-group identity can lead to openness to attitudinal change, even on highly polarized issues. Specifically, we test whether priming a shared identity as a religious person can generate willingness to voice support for same-sex marriage. Methods. We conduct a randomized survey experiment using the SocialSci platform, exposing religious and secular respondents to religious and anonymous primes about same-sex marriage. Results. Individuals who are religious and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 25 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…In addition, federal political parties have seen a number of changes-including the creation of the socially conservative, western-Canadian-based Reform party in 1987; its rebranding as the Canadian Alliance party in 2000; and the merger of that party with the Progressive Conservatives in 2003, which formed the current Conservative party of Canada. Many understand the association between level of religiosity and vote choice as an issue voting effect (Raymond, 2011;Smidt et al, 2010;Van der Brug et al, 2009). Those actively involved with a religious group are more likely to be regularly exposed to right-leaning values within their congregations, families and faith-based schools, as well as within their network of friends and acquaintances who are more likely to share their religious identities and beliefs (Adkins et al, 2013;Ang and Petrocik, 2012;Harrison and Michelson, 2015;Nicolet and Tresch, 2009;O'Neill, 2001;Putnam and Campbell, 2010;Raymond, 2011;Reimer, 2003;Reimer and Wilkinson, 2015;Smidt et al, 2010;Van der Brug et al, 2009). To be clear, however, not all organized religious groups have more conservative teachings and values on issues such as premarital sex, homosexuality, abortion, family life and gender roles.…”
Section: Religiosity Issue Positions and Votingmentioning
confidence: 99%
“…In addition, federal political parties have seen a number of changes-including the creation of the socially conservative, western-Canadian-based Reform party in 1987; its rebranding as the Canadian Alliance party in 2000; and the merger of that party with the Progressive Conservatives in 2003, which formed the current Conservative party of Canada. Many understand the association between level of religiosity and vote choice as an issue voting effect (Raymond, 2011;Smidt et al, 2010;Van der Brug et al, 2009). Those actively involved with a religious group are more likely to be regularly exposed to right-leaning values within their congregations, families and faith-based schools, as well as within their network of friends and acquaintances who are more likely to share their religious identities and beliefs (Adkins et al, 2013;Ang and Petrocik, 2012;Harrison and Michelson, 2015;Nicolet and Tresch, 2009;O'Neill, 2001;Putnam and Campbell, 2010;Raymond, 2011;Reimer, 2003;Reimer and Wilkinson, 2015;Smidt et al, 2010;Van der Brug et al, 2009). To be clear, however, not all organized religious groups have more conservative teachings and values on issues such as premarital sex, homosexuality, abortion, family life and gender roles.…”
Section: Religiosity Issue Positions and Votingmentioning
confidence: 99%
“…Religious beliefs often are deeply rooted and serve to filter new information, whereas religious elites guide the faithful to preferred issue positions and political involvement (Djupe and Calfano 2013b; Djupe and Gilbert 2008; Goidel and Nisbet 2006; Guth et al 1993; Guth et al 1995; Kellstedt et al 1996; Nteta and Wallsten 2012). Previous studies showed that clergy may have an important role in mobilizing religious supporters to participate, influencing political attitudes and beliefs, and serving as opinion leaders in local communities (Goidel and Nisbet 2006; Harrison and Michelson 2015; Jelen 1991; Smidt 2003; Wilcox and Sigelman 2001). 1…”
Section: Perceptions Of Threat To Religious Libertymentioning
confidence: 99%
“…The strong ties of evangelical women to their churches, for example, leads them to emphasize cultural issues in shaping their political party identification (Deckman 2014). Conversely, religious elites’ signs of support for same‐sex marriage move religious respondents to relax their opposition (Harrison and Michelson 2015). But in the case of the 2016 elections, Djupe and Calfano (2018) find that evangelical elites had little influence.…”
Section: The Multiple Political Identities Of Evangelicalsmentioning
confidence: 99%